Trajectory of Massive Particle Around a Magnetically Charged Compact Object in Einstein-Maxwell-dilaton Gravity - Sakkawattana, Chawit; Ponglertsakul, Supakchai (KKU Science Journal, 2025)
In this work, we investigate an orbital motion of massive particle around a static and spherically symmetric magnetically charged object in Einstein-Maxwell-dilaton gravity. This solution has three characteristics parameters, dilaton flux , magnetic charged and dilaton coupling constant . These results provide observational means for understanding physical behaviors of magnetically charged compact object in general relativity.